Personal Names of Mythological Beings in Certain Slavic Curses and Phrases - Раденковић, Љубинко (Poznańskie Studia Slawistyczne, 2012)
The topic of the paper is the interpretation of the motivation for the personal names of certain mythological beings in curses and phrases of Slavic peoples. Curses, as well as certain phraseologisms, can preserve the names long-forgotten in the mythical and religious systems. However, due to their lapidarity and lack of ritual context, these names create the opportunity for different interpretations. The paper analyzes the meanings of names, with a mythological connotation: Maren, Ivan/Jovan,Andjelija,Jana/Janja, and Vid/Vidok.